Identification of meibomian gland testosterone metabolites produced by tissue-intrinsic intracrine deactivation activity - Khanh Tien Nguyen Pham; Takahito Miyake; Tomo Suzuki; Shigeru Kinoshita; Yuki Hamada; Hikari Uehara; Mamiko Machida; Takeshi Nakajima; Emi Hasegawa; Masao Doi (iScience)
Summary: Intracrinology—wherein hormones are synthesized in the organ where they exert their effect without release into circulation—has been described. However, molecular mechanisms of hormone deactivation within intracrine tissue are still largely unknown. The meibomian glands in the eyelids produce oil (meibum) to the ocular surface to prevent dehydration (dry eye). Androgens are generated inside this gland and are crucial for its tissue-homeostasis. However, there is no data showing the presence of androgens in meibum, implying local conversion/deactivation into unknown metabolites. Here, we performed radioactive tracer studies in combination with pharmacological enzyme inhibition, followed by targeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, and found three androgen metabolites—androstanedione, androsterone, and epiandrosterone—in mouse and human meibomian glands. Accounting for the enzymatic conversion, we show tissue-endogenous 3α/3β-ketosteroid reductase expression. We therefore reinforce the idea that androgens are metabolically inactivated within the glands. These metabolite markers may help to assess meibomian local androgen activity using meibum.